2019
DOI: 10.1007/s12035-019-01795-3
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Abnormalities Linked to Interferon, Stress Response, and Energy Metabolism Gene Expression Changes in Older HIV-Positive Patients on Antiretroviral Therapy

Abstract: Neurocognitive impairment (NCI) remains a significant cause of morbidity in human immunodeficiency virus (HIV)-positive individuals despite highly active antiretroviral therapy (HAART). White matter abnormalities have emerged as a key component of age-related neurodegeneration, and accumulating evidence suggests they play a role in HIV-associated neurocognitive disorders. Viral persistence in brain induces chronic inflammation associated with lymphocytic infiltration, microglial proliferation, myelin loss, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 60 publications
4
33
0
Order By: Relevance
“…ISR and EIF2 activation has been implicated in establishing initial viral replication (Jiang et al, 2017). A recent study also found stress response genes, including the ISR-associated gene ATF4, upregulated in the brains of older HIV-positive patients (Solomon et al, 2019). The UPR and consequently EIF2 activation has been implicated in multiple neurodegenerative disorders (Scheper and Hoozemans, 2015), these findings bolster the possibility that UPR and ISR activation play important roles in HAND development or at least the initial response to HIV in the brain.…”
Section: Discussionmentioning
confidence: 88%
“…ISR and EIF2 activation has been implicated in establishing initial viral replication (Jiang et al, 2017). A recent study also found stress response genes, including the ISR-associated gene ATF4, upregulated in the brains of older HIV-positive patients (Solomon et al, 2019). The UPR and consequently EIF2 activation has been implicated in multiple neurodegenerative disorders (Scheper and Hoozemans, 2015), these findings bolster the possibility that UPR and ISR activation play important roles in HAND development or at least the initial response to HIV in the brain.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, white matter alterations in the expression of chemokines, cytokines, and β-defensins correlate with cognitive impairment in patients without HIV encephalitis [ 40 ]. A recent gene expression study also supports inflammatory dysregulation in older HAND patients on ART, as brain tissue from these patients showed upregulation of genes related to interferon signaling, stress, and immune responses, as well as decreased expression of genes involved in cellular metabolism and myelin production [ 41 ]. Overall, these studies shed light on some of the underlying changes contributing to HAND in patients with more controlled infection and further support the hypothesis that subtle neuronal disruption is an important component of modern HAND.…”
Section: Neuroimaging and Neuropathological Studies In Hand Patientsmentioning
confidence: 99%
“…Magnetic resonance and diffusion tensor imaging studies show numerous alterations including corpus callosum thinning and reduced blood flow in white matter (Hoare et al, 2010; Tate et al, 2011). Transcriptome analyses demonstrate downregulation of transcripts critical for oligodendrocyte (OL) maturation and myelination despite cART (Borjabad et al, 2011; Solomon et al, 2020). While the underlying mechanisms remain unclear, HIV and/or cART may play a role in these persistent white matter pathologies.…”
Section: Introductionmentioning
confidence: 99%